Analisis Permasalahan Pembiayaan UMKM di Indonesia - Nurhidayat, R. (Jurnal Kajian Ekonomi dan Keuangan, 2011)
Micrp small and medium enterprises (SMEs) have a strategic role in Indonesia's economy. Therefore, this sector requires adequate financial supprt. By using Granger causality test, this study show that credit to small businesses caused economic growth. The data used in this study from March 2001 to December 2009. Data obtained through the Central Bureau of Statistics, Ministry of Cooperatives and SMEs, as well as Bank Indonesia. This study also found evidence that government-owned banks have been allocated large funds to assist SMEs. However, the credit growth is still less than the credit growth of the foreign and joint banks which are expanding its business into the SME sector. The expanson of foreign and joint banks in the SME sector can be seen from the high growth in credit to this sector. In additon, this study analyzed alternative solutions for financing SMEs. The Government needs to promote microfinance institutions as an alternative solution for SME financing.